Treatment Efficiency by means of a Nonthermal Plasma Combined with Heterogeneous Catalysis of Odoriferous Volatile Organic Compounds Emissions from the Thermal Drying of Landfill Leachates - Daniel Almarcha; Manuel Almarcha; Elena Jimenez-Coloma; Laura Vidal; Montserrat Puigcercós; Iban Barrutiabengoa (Journal of Engineering)
The objective of the present work was to assess the odoriferous volatile organic compounds depuration efficiency of an experimental nonthermal plasma coupled to a catalytic system used for odor abatement of real emissions from a leachate thermal drying plant installed in an urban solid waste landfill. VOC screening was performed by means of HRGC-MS analysis of samples taken at the inlet and at the outlet of the nonthermal plasma system. Odor concentration by means of dynamic olfactometry, total organic carbon, mercaptans, NH3, and H2S were also determined in order to assess the performance of the system throughout several days. Three plasma frequencies (100, 150, and 200 Hz) and two catalyst temperatures (150°C and 50°C) were also tested. Under conditions of maximum capacity of the treatment system, the results show VOC depuration efficiencies around 69%, with average depuration efficiencies between 44 and 95% depending on the chemical family of the substance. Compounds belonging to the following families have been detected in the samples: organic acids, alcohols, ketones, aldehydes, pyrazines, and reduced sulphur compounds, among others. Average total organic carbon removal efficiency was 88%, while NH3 and H2S removal efficiencies were 88% and 87%, respectively, and odor concentration abatement was 78%.